Compliance with Agreements in Cross-Cultural Transactions: Some Analytical Issues - Thompson, Allan G. (Journal of International Business Studies, 1996)
Assessing whether the other party is likely to fulfil all obligations can be arduous when a transaction is international. The mechanisms that underpin compliance with agreements, and the functional detail of these mechanisms, may vary in relative importance between countries, perplexing the foreign operative. Additionally, a foreigner may suffer from informational constraints, communications distortions, and difficulty in achieving full acceptance in the local business culture.